Solid-state battery and method for manufacturing solid-state battery
By integrating an external electrode component intrusion portion between the electrodes and the embedded layer, the adhesion and moisture resistance of solid batteries are enhanced, addressing the issue of moisture intrusion and performance deterioration.
Patent Information
- Application Number
- JP2023117512
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-30
AI Technical Summary
The adhesion between the laminated body and external electrodes in solid batteries is insufficient, leading to moisture intrusion and deterioration of battery performance.
Incorporating an external electrode component intrusion portion between the external electrodes and the embedded layer, which enhances adhesion and moisture resistance by extending metal and glass components between the electrodes and the embedded layer.
The solution improves adhesion and moisture resistance, reducing water intrusion and maintaining battery performance by preventing short circuits and enhancing the lifespan of solid batteries.
Smart Images

Figure 2025014727000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solid-state battery and a method for manufacturing a solid-state battery. [Background technology]
[0002] For example, as a solid-state battery, an all-solid-state lithium ion secondary battery is known that includes a laminate of a positive electrode layer, an electrolyte layer, and a negative electrode layer, and a pair of terminal electrodes connected to the positive electrode layer and the negative electrode layer, respectively (Patent Document 1). With regard to such a solid-state battery, a technique is known in which an electrode separator is provided between the terminal electrode connected to the negative electrode layer and the positive electrode layer, and between the terminal electrode connected to the positive electrode layer and the negative electrode layer, respectively (Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-182945 A [Patent Document 2] JP 2023-22219 A Summary of the Invention [Problem to be solved by the invention]
[0004] A solid-state battery includes a laminate including a positive electrode layer and a negative electrode layer (also called "electrode layers") as power generating elements and a solid electrolyte layer interposed therebetween, and external electrodes provided on both end surfaces of the laminate and connected to the positive electrode layer and the negative electrode layer, respectively. The laminate includes layers of solid electrolyte or glass (also called "embedding layers") provided as electrode separators between the external electrodes and each of the positive electrode layer and the negative electrode layer.
[0005] In conventional solid-state batteries, the adhesion between the laminate, which is the power generating element, and the external electrodes provided on both end faces of the laminate is insufficient, so high moisture resistance cannot be obtained, and the battery performance can deteriorate due to the penetration of moisture into the laminate.
[0006] In one aspect, the present invention aims to realize a solid-state battery having external electrodes with high adhesion and excellent moisture resistance. [Means for solving the problem]
[0007] In one aspect, a solid-state battery is provided including a solid electrolyte layer, an electrode layer provided on a first surface side of the solid electrolyte layer, an external electrode provided on a first end side of the solid electrolyte layer, a buried layer provided between the electrode layer and the external electrode on the first surface side of the solid electrolyte layer, and an external electrode component penetration portion extending from the external electrode between the solid electrolyte layer and the buried layer and including a component of the external electrode.
[0008] In another aspect, a method for producing such a solid-state battery is provided. Effect of the Invention
[0009] On the one hand, it will be possible to realize a solid-state battery with strong adhesion between external electrodes and excellent moisture resistance. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a diagram illustrating an example of a solid-state battery. [Diagram 2] 1A to 1C are diagrams illustrating an example of a method for manufacturing a solid-state battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] Fig. 1 is a diagram for explaining an example of a solid-state battery, which diagrammatically shows a cross-sectional view of a main part of an example of a solid-state battery. The solid-state battery 1 shown in Fig. 1 is an example of a lithium-ion battery. The solid-state battery 1 includes a laminate 10, an external electrode 20, and an external electrode 30. The laminate 10 is an example of a power generating element of the solid-state battery 1. The external electrode 20 and the external electrode 30 are provided so as to cover the opposing end faces 10a and 10b of the laminate 10, respectively.
[0012] The laminate 10 has a positive electrode layer 11, an opposing negative electrode layer 12, and a solid electrolyte layer 13 interposed therebetween. Here, as an example, the laminate 10 having one positive electrode layer 11, one negative electrode layer 12, and one solid electrolyte layer 13 is illustrated.
[0013] The positive electrode layer 11 is provided in a partial region on one surface 13a side of the solid electrolyte layer 13. A part of the side surface of the positive electrode layer 11 extends to one end 13c of the solid electrolyte layer 13 and is exposed at one end surface 10a of the laminate 10.
[0014] The negative electrode layer 12 is provided in a partial region on the other surface 13b side opposite to the one surface 13a side of the solid electrolyte layer 13. A part of the side surface of the negative electrode layer 12 extends to the other end 13d opposite to the one end 13c of the solid electrolyte layer 13 and is exposed at the other end surface 10b opposite to the one end surface 10a of the laminate 10.
[0015] The positive electrode layer 11 and the negative electrode layer 12 are provided so as to partially overlap each other with the solid electrolyte layer 13 interposed therebetween. The external electrode 20 provided on the end face 10a side of the laminate 10, i.e., the end 13c side of the solid electrolyte layer 13, extends to the end 13c and is connected to a part of the side surface of the positive electrode layer 11 exposed at the end face 10a. The external electrode 20 functions as a positive electrode terminal of the solid-state battery 1.
[0016] The external electrode 30 provided on the end face 10b side of the laminate 10, i.e., the end 13d side of the solid electrolyte layer 13, extends to the end 13d and is connected to a part of the side surface of the negative electrode layer 12 exposed at the end face 10b. The external electrode 30 functions as a negative electrode terminal of the solid-state battery 1.
[0017] The laminate 10 further includes a buried layer 14. The buried layer 14 is provided on the surface 13b side of the solid electrolyte layer 13 on which the negative electrode layer 12 is provided and on the surface 13a side on which the positive electrode layer 11 is provided.
[0018] The embedded layer 14 is provided between the external electrode 20 connected to the positive electrode layer 11 and the negative electrode layer 12, and between the external electrode 30 connected to the negative electrode layer 12 and the positive electrode layer 11. That is, the embedded layer 14 is provided in a region from an end 13c of the solid electrolyte layer 13 in contact with the external electrode 20 to the side surface of the negative electrode layer 12 facing the end 13c, and in a region from an end 13d of the solid electrolyte layer 13 in contact with the external electrode 30 to the side surface of the positive electrode layer 11 facing the end 13d.
[0019] The embedded layer 14 electrically separates the positive external electrode 20 from the negative electrode layer 12, and electrically separates the negative external electrode 30 from the positive electrode layer 11. The embedded layer 14 is an example of an electrode separator (also referred to as a blank layer, etc.).
[0020] The laminate 10 further has a moisture-proof layer 15. The moisture-proof layer 15 is provided so as to cover the surface of the laminate 10 except for the end faces 10a and 10b. That is, the moisture-proof layer 15 is provided so that a part of the side surface of the positive electrode layer 11 connected to the external electrode 20 is exposed from the end face 10a of the laminate 10, and a part of the side surface of the negative electrode layer 12 connected to the external electrode 30 is exposed from the end face 10b of the laminate 10.
[0021] The external electrode 20 provided on the end face 10a of the laminate 10 and the external electrode 30 provided on the end face 10b thereof are, for example, glass-based external electrodes containing metal and glass. The external electrodes 20 and 30 may be made of the same material, i.e., materials containing the same metal and glass. Alternatively, the external electrodes 20 and 30 may be made of different materials, i.e., materials containing different metals or different glasses.
[0022] The solid-state battery 1 including the laminate 10 as described above further includes an external electrode component insertion portion 40 and an external electrode component insertion portion 50. The external electrode component penetration portion 40 extends from the external electrode 20 connected to the positive electrode layer 11 between the adjacent solid electrolyte layer 13 and buried layer 14. The external electrode component penetration portion 40 contains a component of the external electrode 20, i.e., at least one of the metal and glass contained in the external electrode 20, for example, both metal and glass components. The external electrode component penetration portion 40 is a positive electrode side external electrode component penetration portion 40 that contains a component of the positive external electrode 20.
[0023] The external electrode component penetration portion 50 extends from the external electrode 30 connected to the negative electrode layer 12 to between the adjacent solid electrolyte layer 13 and buried layer 14. The external electrode component penetration portion 50 contains a component of the external electrode 30, i.e., at least one of the metal and glass contained in the external electrode 30, for example, both metal and glass components. The external electrode component penetration portion 50 is the external electrode component penetration portion 50 on the negative electrode side that contains a component of the negative external electrode 30.
[0024] The external electrode component penetration portion 40 on the positive electrode side and the external electrode component penetration portion 50 on the negative electrode side contain either the same type of components or different types of components, depending on whether the external electrodes 20 and external electrodes 30 connected to them, respectively, are made of the same type of materials or different types of materials.
[0025] The penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side, i.e., the penetration depth Dp from the external electrode 20 connected to the positive electrode layer 11 or from the end 13c of the solid electrolyte layer 13 to which the positive electrode layer 11 extends, is set to a certain value or more. For example, the penetration depth Dp of the external electrode component penetration portion 40 is set to 12 μm or more. However, it is desirable to set the upper limit of the penetration depth Dp of the external electrode component penetration portion 40 to a depth that does not reach the negative electrode layer 12. This is because if the external electrode component penetration portion 40 extending from the external electrode 20 connected to the positive electrode layer 11 reaches the negative electrode layer 12, a short circuit may occur.
[0026] The penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side, i.e., the penetration depth Dn from the external electrode 30 connected to the negative electrode layer 12 or from the end 13d of the solid electrolyte layer 13 to which the negative electrode layer 12 extends, is set to a certain value or more. For example, the penetration depth Dn of the external electrode component penetration portion 50 is set to 12 μm or more. However, it is preferable that the penetration depth Dn of the external electrode component penetration portion 50 has an upper limit of a depth that does not reach the positive electrode layer 11. This is because if the external electrode component penetration portion 50 extending from the external electrode 30 connected to the negative electrode layer 12 reaches the positive electrode layer 11, a short circuit may occur.
[0027] The penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side may have the same value or may have different values. The solid-state battery 1 has, for example, the configuration described above.
[0028] In the solid-state battery 1, one or both of the positive electrode layer 11 and the negative electrode layer 12 are also referred to as "electrode layers." The surface 13a of the solid electrolyte layer 13 is also referred to as the "first surface," and the end 13d is also referred to as the "first end." Alternatively, the surface 13b of the solid electrolyte layer 13 is also referred to as the "first surface," and the end 13c is also referred to as the "first end."
[0029] Here, the laminate 10 of the solid-state battery 1 is exemplified as having one positive electrode layer 11, one negative electrode layer 12, and one solid electrolyte layer 13, but the laminate 10 may include a plurality of structures in which the positive electrode layer 11 and the negative electrode layer 12 are laminated with the solid electrolyte layer 13 interposed therebetween. In this case, too, an embedded layer 14 is provided between the negative electrode layer 12 and the external electrode 20 of the laminate 10, and between the positive electrode layer 11 and the external electrode 30, respectively, and a moisture-proof layer 15 is provided on the surface excluding the end face 10a and the end face 10b. Then, the above-mentioned external electrode component intrusion portion 40 or the external electrode component intrusion portion 50 is provided between the solid electrolyte layer 13 adjacent to each of the external electrode 20 and the external electrode 30 and the embedded layer 14.
[0030] The configuration of the solid-state battery 1 will be further described. For the solid electrolyte layer 13 of the laminate 10 of the solid-state battery 1, for example, an oxide solid electrolyte is used. As the oxide solid electrolyte, for example, LAGP, which is one type of NASICON (Na super ionic conductor)-type (also referred to as "NASICON type") oxide solid electrolyte, is used. LAGP is an oxide solid electrolyte represented by the general formula Li 1+x Al x Ge 2-x (PO4)3 (0 < x ≤ 1). In addition, for the solid electrolyte layer 13, a sulfide solid electrolyte such as Li2S (lithium sulfide)-P2S5 (diphosphorus pentasulfide) may be used.
[0031] The positive electrode layer 11 of the laminate 10 contains a positive electrode active material, a conductive assistant, and a solid electrolyte. For the solid electrolyte of the positive electrode layer 11, an oxide solid electrolyte or a sulfide solid electrolyte, for example, the same kind of material as the solid electrolyte used for the solid electrolyte layer 13, is used. As the positive electrode active material of the positive electrode layer 11, for example, Li2CoP2O7 (lithium cobalt pyrophosphate, also referred to as "LCPO") etc. are used. As the conductive assistant of the positive electrode layer 11, for example, carbon materials such as carbon fiber, carbon black, graphite, graphene, or carbon nanotubes, or conductive materials such as iron silicide are used.
[0032] The negative electrode layer 12 of the laminate 10 contains a negative electrode active material, a conductive assistant, and a solid electrolyte. For the solid electrolyte of the negative electrode layer 12, an oxide solid electrolyte or a sulfide solid electrolyte, for example, the same kind of material as the solid electrolyte used for the solid electrolyte layer 13, is used. As the negative electrode active material of the negative electrode layer 12, for example, TiO2 (titanium oxide), Nb2O5 (niobium pentoxide) etc. are used. In addition, as the negative electrode active material of the negative electrode layer 12, Li3V2(PO4)3 (lithium vanadium phosphate), Li4Ti5O 12 (lithium titanate) etc. may be used. As the conductive assistant of the negative electrode layer 12, for example, carbon materials such as carbon fiber, carbon black, graphite, graphene, or carbon nanotubes, or conductive materials such as iron silicide are used.
[0033] In the solid-state battery 1, during charging, lithium ions are conducted from the positive electrode layer 11 through the solid electrolyte layer 13 to the negative electrode layer 12 and are incorporated therein, and during discharging, lithium ions are conducted from the negative electrode layer 12 to the positive electrode layer 11 through the solid electrolyte layer 13 and are incorporated therein. In the solid-state battery 1, charging and discharging operations are realized by such lithium ion conduction in the laminate 10 of the power generating element.
[0034] For example, an insulating glass material is used for the buried layer 14 of the laminate 10. An insulating glass material is used to make the buried layer 14 insulating. In addition, various insulating materials such as solid electrolytes and ceramics may be used for the buried layer 14. The insulating property of the buried layer 14 refers to a property that has no effect on the lithium ion conduction and electron conduction in the laminate 10 or has a sufficiently low effect.
[0035] For example, the embedded layer 14 is made of an insulating material having a higher hardness than the solid electrolytes used in the solid electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12. For example, the embedded layer 14 is made of an insulating material having low permeability to moisture or gases such as hydrogen and oxygen, and capable of achieving good sealing. The embedded layer 14 has a function of protecting the solid electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12 from external forces and the outside air.
[0036] The moisture-proof layer 15 of the laminate 10 is made of an insulating material having moisture resistance. For example, the same insulating material as that of the embedding layer 14 is used for the moisture-proof layer 15. That is, the moisture-proof layer 15 is made of an insulating material having a higher hardness than the solid electrolyte used in the solid electrolyte layer 13, etc., and an insulating material having low moisture and gas permeability and good sealing properties. The moisture-proof layer 15 has a function of protecting the solid electrolyte layer 13, the positive electrode layer 11, and the negative electrode layer 12 from external forces and the outside air.
[0037] Additionally, the moisture-proof layer 15 may be made of an insulating material such as SiO2 (silicon oxide) or SiN (silicon nitride). The external electrodes 20 and 30 are made of glass-based materials including metal and glass. The metal of the external electrodes 20 and 30 may be, for example, Ag (silver). Other metals such as Cu (copper), Au (gold), and Ni (nickel) may be used. Various glass materials may be used for the glass of the external electrodes 20 and 30. For example, chalcogenide glass, silicate glass, metallic glass, and the like may be used for the glass of the external electrodes 20 and 30. For example, Te (tellurium)-based glass, Te-V (vanadium)-based glass, Te-V-Bi (bismuth)-based glass, and the like may be used for the glass of the external electrodes 20 and 30.
[0038] The external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 respectively contain components of the positive external electrode 20 and the negative external electrode 30. For example, the external electrode component intrusion portion 40 contains both the metal and glass components of the positive external electrode 20, and the external electrode component intrusion portion 50 contains both the metal and glass components of the negative external electrode 30. For example, in a case where both the external electrodes 20 and 30 contain Ag as the metal and a chalcogenide glass such as Te-based glass as the glass, the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 are configured to contain Ag, which is a metal component, and chalcogen such as Te, which is a glass component.
[0039] In the solid-state battery 1, the external electrode component intrusion portion 40 extending from the external electrode 20 between the solid electrolyte layer 13 and the embedded layer 14 improves the adhesion between the external electrode 20 and the end face 10a of the laminate 10. Also, in the solid-state battery 1, the external electrode component intrusion portion 50 extending from the external electrode 30 between the solid electrolyte layer 13 and the embedded layer 14 improves the adhesion between the external electrode 30 and the end face 10b of the laminate 10. This improves the moisture resistance of the solid-state battery 1, and prevents moisture from infiltrating into the laminate 10 from between the external electrode 20 and the external electrode 30 and the laminate 10.
[0040] The solid electrolytes used in the laminate 10, for example, the solid electrolyte contained in the solid electrolyte layer 13 as well as the solid electrolytes contained in the positive electrode layer 11 and the negative electrode layer 12, have a property of being relatively susceptible to reaction with moisture. In addition, the active material contained in the positive electrode layer 11 or the negative electrode layer 12 may also react with moisture. Therefore, when moisture penetrates into the inside of the laminate 10 from between the external electrode 20 and the laminate 10 or between the external electrode 30 and the laminate 10, the battery performance, for example, the charge / discharge characteristics and the lifespan of the battery, may deteriorate.
[0041] In contrast, in the solid-state battery 1, external electrode component intrusion portions 40 and external electrode component intrusion portions 50 are provided, which extend from the external electrodes 20 and 30 between the solid electrolyte layer 13 and the embedded layer 14. This enhances the adhesion between the external electrodes 20 and 30 and the laminate 10, and improves the moisture resistance of the solid-state battery 1. This suppresses the intrusion of moisture into the laminate 10 of the solid-state battery 1 and the resulting deterioration of battery performance.
[0042] The configuration in which the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 are provided realizes a solid-state battery 1 having high adhesion and excellent moisture resistance between the external electrodes 20 and 30. A high-performance solid-state battery 1 having excellent moisture resistance and suppressing deterioration of battery performance caused by moisture intrusion is realized.
[0043] The adhesion between the external electrode 20 and the external electrode 30 and the moisture resistance of the solid-state battery 1 tend to increase as the penetration depth Dp of the external electrode component penetration portion 40 and the penetration depth Dn of the external electrode component penetration portion 50 increase. However, the external electrode component penetration portion 40 and the external electrode component penetration portion 50 may contain metal components of the external electrode 20 and the external electrode 30, respectively. Therefore, in order to avoid a short circuit with the negative electrode layer 12, it is desirable that the upper limit of the penetration depth Dp of the external electrode component penetration portion 40 is set to a depth that does not reach the negative electrode layer 12. Similarly, in order to avoid a short circuit with the positive electrode layer 11, it is desirable that the upper limit of the penetration depth Dn of the external electrode component penetration portion 50 is set to a depth that does not reach the positive electrode layer 11.
[0044] The solid-state battery 1 may have a configuration having either the external electrode component penetration portion 40 or the external electrode component penetration portion 50. Even with such a configuration, it is possible to obtain a certain effect of increasing the adhesion of the external electrode 30 or the external electrode 20 and a certain effect of increasing the moisture resistance of the solid-state battery 1, compared to a configuration not having the external electrode component penetration portion 40 or the external electrode component penetration portion 50.
[0045] Next, a method for manufacturing the solid-state battery 1 having the above configuration will be described. 2A and 2B are diagrams for explaining an example of a method for manufacturing a solid-state battery. Fig. 2A is a schematic cross-sectional view of a main part of an example of a laminate formation step. Fig. 2B is a schematic cross-sectional view of a main part of an example of an external electrode paste application step. Fig. 2C is a schematic cross-sectional view of a main part of an example of a heat treatment (baking) step.
[0046] 2(A) is formed. In forming the laminate 10, for example, pastes for the positive electrode layer 11, the negative electrode layer 12, the solid electrolyte layer 13, the buried layer 14, and the moisture-proof layer 15 are prepared in advance.
[0047] As the paste for the positive electrode layer 11, a paste containing a positive electrode active material such as LCPO, a solid electrolyte such as LAGP, a conductive assistant such as a carbon material, as well as a binder, a plasticizer, a dispersant, a diluent, and the like is prepared.
[0048] The paste for the negative electrode layer 12 contains a negative electrode active material such as TiO2 or Nb2O5, a solid electrolyte such as LAGP, a conductive assistant such as a carbon material, as well as a binder, a plasticizer, a dispersant, a diluent, and the like.
[0049] As the paste for the solid electrolyte layer 13, a paste containing a solid electrolyte such as LAGP, as well as a binder, a plasticizer, a dispersant, a diluent, and the like is prepared. A paste containing an insulating glass material such as a so-called low-melting-point glass that is melted and sintered at about 600° C. is prepared as the paste for the buried layer 14. In addition, a paste containing an insulating material such as a solid electrolyte or ceramics may be prepared as the paste for the buried layer 14. A ceramic material such as particulate Al2O3 (aluminum oxide) may be added to the paste for the buried layer 14.
[0050] As the paste for the moisture-proof layer 15, a paste similar to that for the embedding layer 14 is prepared. The prepared pastes for the positive electrode layer 11, the negative electrode layer 12, the solid electrolyte layer 13, the embedding layer 14, and the moisture-proof layer 15 are applied in the stacking order shown in the laminate 10 in Fig. 2(A). Alternatively, each sheet formed by applying each paste onto a support such as a PET (polyethylene terephthalate) film is laminated in the stacking order shown in the laminate 10 in Fig. 2(A).
[0051] The structure obtained by applying the paste or the structure obtained by laminating the sheets in this manner has end faces 10a and 10b at which part of the side surfaces of the pastes for the positive electrode layer 11 and the negative electrode layer 12, or the sheets for the positive electrode layer 11 and the negative electrode layer 12 formed therefrom, are exposed. To obtain such a structure, the structure after applying the paste or laminating the sheets may be cut as necessary.
[0052] Then, a heat treatment (also called "degreasing") is performed to remove organic components such as binders in the paste or sheet, and a heat treatment (also called "firing") is further performed to sinter the solid electrolyte, glass, ceramics, etc. in the paste or sheet.
[0053] By such heat treatments of degreasing and firing, the positive electrode layer 11, the negative electrode layer 12, the solid electrolyte layer 13, the embedding layer 14, and the moisture-proof layer 15 are formed. That is, the positive electrode layer 11 is formed from the paste or sheet for the positive electrode layer 11. The negative electrode layer 12 is formed from the paste or sheet for the negative electrode layer 12. The solid electrolyte layer 13 is formed from the paste or sheet for the solid electrolyte layer 13. The embedding layer 14 is formed from the paste or sheet for the embedding layer 14. The moisture-proof layer 15 is formed from the paste or sheet for the moisture-proof layer 15. In this way, the laminate 10 as shown in FIG. 2(A) is formed.
[0054] When using SiN or the like for the moisture-proof layer 15, a structure in which the positive electrode layer 11, the negative electrode layer 12, the solid electrolyte layer 13 and the embedded layer 14 are laminated is formed according to the above example (paste coating or sheet lamination, and heat treatment for degreasing and firing), and then the moisture-proof layer 15 of SiN or the like is formed on the surface of the structure.
[0055] After forming the laminate 10 as shown in FIG. 2(A), the external electrodes 20 and 30, as well as the external electrode component insertion portions 40 and external electrode component insertion portions 50, are formed as shown in FIG. 2(B) and FIG. 2(C).
[0056] In forming the external electrodes 20 and 30, a paste material containing a powder containing a predetermined metal such as Ag and a powder containing a predetermined glass is prepared. The prepared paste material is applied to the end faces 10a and 10b of the laminate 10, where parts of the side faces of the positive electrode layer 11 and the negative electrode layer 12 are exposed. As a result, the external electrode paste 21 and the external electrode paste 31 are formed on the end faces 10a and 10b of the laminate 10, respectively, as shown in FIG. 2(B).
[0057] The external electrode paste 21 and the external electrode paste 31 may be formed using the same type of paste material, or the external electrode paste 21 and the external electrode paste 31 may be formed using different types of paste materials.
[0058] The external electrode paste 21 and the external electrode paste 31 formed on the end face 10a side and the end face 10b side of the laminate 10, respectively, are subjected to a heat treatment 60 under predetermined conditions, as shown in Fig. 2(C). That is, the external electrode paste 21 on the end face 10a side of the laminate 10 and the external electrode paste 31 on the end face 10b side are baked by the heat treatment 60. As a result, an external electrode 20 containing a predetermined metal and glass is formed from the external electrode paste 21 on the end face 10a side of the laminate 10. An external electrode 30 containing a predetermined metal and glass is formed from the external electrode paste 31 on the end face 10b side of the laminate 10.
[0059] In the heat treatment 60 for forming the external electrodes 20 and 30, metal and glass components contained in the external electrodes 20 or the external electrode paste 21 diffuse and infiltrate between the solid electrolyte layer 13 and the buried layer 14. This forms an external electrode component intrusion portion 40 as shown in Fig. 2(C), that is, the external electrode component intrusion portion 40 extending from the external electrode 20 between the solid electrolyte layer 13 and the buried layer 14. At this time, the intrusion depth (corresponding to Dp in Fig. 1) of the external electrode component intrusion portion 40 from the end 13c of the solid electrolyte layer 13 (or the end face 10a of the laminate 10) can be changed or adjusted depending on the conditions of the heat treatment 60.
[0060] Furthermore, in the heat treatment 60 for forming the external electrodes 20 and 30, metal and glass components contained in the external electrodes 30 or the external electrode paste 31 diffuse and infiltrate between the solid electrolyte layer 13 and the buried layer 14. This forms an external electrode component intrusion portion 50 as shown in Fig. 2(C), that is, an external electrode component intrusion portion 50 extending from the external electrode 30 between the solid electrolyte layer 13 and the buried layer 14. At this time, the intrusion depth (corresponding to Dn in Fig. 1) of the external electrode component intrusion portion 50 from the end 13d of the solid electrolyte layer 13 (or the end face 10b of the laminate 10) can be changed or adjusted depending on the conditions of the heat treatment 60.
[0061] The heat treatment 60 for forming the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 may include a heat treatment whose conditions are set for the purpose of forming the external electrodes 20 and 30, as well as a heat treatment performed under the same or different conditions subsequent to the heat treatment. Alternatively, the heat treatment 60 for forming the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 may include a heat treatment whose conditions are set for the purpose of forming the external electrodes 20 and 30, as well as a heat treatment performed under the same or different conditions after the heat treatment. Such a heat treatment 60 may allow metal and glass components to infiltrate between the solid electrolyte layer 13 and the buried layer 14, thereby forming the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50.
[0062] Although not shown here, a plating layer of Ni, Sn (tin) or the like may be formed by electrolytic plating or the like on the surfaces of the external electrodes 20 and 30 formed by the heat treatment 60. For example, a Ni plating layer is formed on the surfaces of the external electrodes 20 and 30, and a Sn plating layer is formed on the surface of the Ni plating layer.
[0063] Through the steps described above, the solid-state battery 1 having the configuration shown in FIG. 1 is manufactured. In the solid-state battery 1, the external electrode component penetration portion 40 extending from the external electrode 20 between the solid electrolyte layer 13 and the embedded layer 14 improves the adhesion between the external electrode 20 and the end face 10a of the laminate 10. Also, in the solid-state battery 1, the external electrode component penetration portion 50 extending from the external electrode 30 between the solid electrolyte layer 13 and the embedded layer 14 improves the adhesion between the external electrode 30 and the end face 10b of the laminate 10.
[0064] This improves moisture resistance in the solid-state battery 1, inhibits moisture from penetrating into the laminate 10 from between the external electrodes 20 and 30 and the laminate 10, and inhibits deterioration of battery performance due to moisture penetration into the laminate 10, which is a power generating element. A solid-state battery 1 having high adhesion between the external electrodes 20 and 30 and excellent moisture resistance is realized. A high-performance solid-state battery 1 having excellent moisture resistance and inhibiting deterioration of battery performance due to moisture penetration is realized.
[0065] Next, the results of evaluating the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side, as well as the life of the solid-state battery 1 under high humidity, for samples prepared by changing the conditions of the heat treatment 60 when forming the external electrodes 20 and 30, will be described.
[0066] <Sample> [No.1] The laminate 10 (FIG. 2(A)) using glass for the embedding layer 14 as described above was prepared, and the same type of glass-based external electrode paste 21 and external electrode paste 31 containing a predetermined metal and glass were applied to the end face 10a side and end face 10b side of the laminate 10 (FIG. 2(B)). Heat treatment 60 was performed under conditions of a temperature of 363° C. and a holding time of 10 minutes to form the external electrodes 20 and 30 (FIG. 2(C)). This heat treatment 60 formed the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 extending from each of the external electrodes 20 and 30 to between the solid electrolyte layer 13 and the embedding layer 14 (FIG. 2(C)). As a result, a solid-state battery 1 (FIG. 1) of Sample No. 1 was obtained.
[0067] [No.2] The laminate 10 (FIG. 2(A)) using glass for the embedding layer 14 as described above was prepared, and the same type of glass-based external electrode paste 21 and external electrode paste 31 containing a predetermined metal and glass were applied to the end face 10a side and end face 10b side of the laminate 10 (FIG. 2(B)). Heat treatment 60 was performed under conditions of a temperature of 363° C. and a holding time of 40 minutes to form the external electrodes 20 and 30 (FIG. 2(C)). This heat treatment 60 formed the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 extending from each of the external electrodes 20 and 30 to between the solid electrolyte layer 13 and the embedding layer 14 (FIG. 2(C)). As a result, a solid-state battery 1 (FIG. 1) of Sample No. 2 was obtained.
[0068] [No.3] The laminate 10 (FIG. 2(A)) using glass for the embedding layer 14 as described above was prepared, and the same type of glass-based external electrode paste 21 and external electrode paste 31 containing a predetermined metal and glass were applied to the end face 10a side and end face 10b side of the laminate 10 (FIG. 2(B)). Heat treatment 60 was performed under conditions of a temperature of 370° C. and a holding time of 40 minutes to form the external electrodes 20 and 30 (FIG. 2(C)). This heat treatment 60 formed the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 extending from each of the external electrodes 20 and 30 to between the solid electrolyte layer 13 and the embedding layer 14 (FIG. 2(C)). As a result, a solid-state battery 1 (FIG. 1) of Sample No. 3 was obtained.
[0069] [No.4] The laminate 10 (FIG. 2(A)) using glass for the embedding layer 14 as described above was prepared, and the same type of glass-based external electrode paste 21 and external electrode paste 31 containing a predetermined metal and glass were applied to the end face 10a side and end face 10b side of the laminate 10 (FIG. 2(B)). Heat treatment 60 was performed under conditions of a temperature of 380° C. and a holding time of 40 minutes to form the external electrodes 20 and 30 (FIG. 2(C)). This heat treatment 60 formed the external electrode component intrusion portion 40 and the external electrode component intrusion portion 50 extending from each of the external electrodes 20 and 30 to the solid electrolyte layer 13 and the embedding layer 14 (FIG. 2(C)). As a result, a solid-state battery 1 (FIG. 1) of Sample No. 4 was obtained.
[0070] <Evaluation> [Penetration depth of external electrode component penetration part] An elemental analysis was performed on the cross section of the solid state battery 1 of Sample No. 1-4 to measure the region in which the metal and glass components of the external electrode 20 are distributed, which extends from the external electrode 20 connected to the positive electrode layer 11 to between the solid electrolyte layer 13 and the buried layer 14. This elemental analysis confirmed that a region in which the metal and glass components are distributed extends from the external electrode 20 between the solid electrolyte layer 13 and the buried layer 14, and an external electrode component penetration part 40 is formed. From the measured distribution region of the metal and glass components, the penetration depth Dp of the external electrode component penetration part 40 on the positive electrode side was obtained.
[0071] Similarly, elemental analysis was performed on the cross section of the solid-state battery 1 of Sample No. 1-4 to measure the region in which the metal and glass components of the external electrode 30 are distributed, which extends from the external electrode 30 connected to the negative electrode layer 12 to between the solid electrolyte layer 13 and the buried layer 14. This elemental analysis confirmed that a region in which the metal and glass components are distributed extends from the external electrode 30 between the solid electrolyte layer 13 and the buried layer 14, and an external electrode component penetration part 50 is formed. From the measured distribution region of the metal and glass components, the penetration depth Dn of the external electrode component penetration part 50 on the negative electrode side was obtained.
[0072] [Lifespan under high humidity conditions] The charge-discharge measurements were performed on the solid-state batteries 1 of Samples No. 1-4 under conditions of high humidity at a temperature of 85° C. and a relative humidity (RH) of 85%. From the results of the charge-discharge measurements, the lifespan (deterioration start time) of the solid-state batteries 1 of Samples No. 1-4 was calculated.
[0073] The penetration depth Dp [μm] of the external electrode component penetration portion 40 on the positive electrode side, the penetration depth Dn [μm] of the external electrode component penetration portion 50 on the negative electrode side, and the life [h] under high humidity (85°C, 85% RH) obtained for the solid-state batteries 1 of Samples No. 1-4 are shown in Table 1.
[0074] [Table 1]
[0075] From the results of sample No. 1-2, even if the temperature of the heat treatment 60 was the same, a longer holding time tended to increase the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side, and thus tended to increase the lifespan.
[0076] From the results of sample No. 2-4, even if the holding time of the heat treatment 60 was the same, a higher temperature tended to increase the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side, and tended to increase the lifespan.
[0077] From Table 1, it was found that in the solid-state battery 1, the higher the temperature of the heat treatment 60 and the longer the holding time, the larger the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side become, and the longer the life becomes. It can also be said that the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side can be changed or adjusted depending on the conditions of the heat treatment 60.
[0078] From Table 1, it can be said that when the penetration depth Dp of the external electrode component penetration portion 40 on the positive electrode side and the penetration depth Dn of the external electrode component penetration portion 50 on the negative electrode side are 12 μm or more, the life of the solid-state battery 1 is extended and deterioration of the battery performance is suppressed.
[0079] Therefore, in order to increase the moisture resistance of the solid-state battery 1 and thereby suppress deterioration of battery performance, it is preferable to provide an external electrode component penetration portion 40 having a penetration depth Dp of 12 μm or more from the external electrode 20, and it is preferable to provide an external electrode component penetration portion 50 having a penetration depth Dn of 12 μm or more from the external electrode 30. However, in order to avoid short circuits, it is preferable to set the penetration depth Dp of the external electrode component penetration portion 40 at an upper limit to a depth that does not reach the negative electrode layer 12, and it is preferable to set the penetration depth Dn of the external electrode component penetration portion 50 at an upper limit to a depth that does not reach the positive electrode layer 11. [Explanation of symbols]
[0080] 1 solid state battery 10 Laminate 10a, 10b end face 11 Positive electrode layer 12 Negative electrode layer 13 Solid electrolyte layer 13a, 13b side 13c, 13d end 14 Embedding Layer 15 Moisture barrier 20, 30 external electrode 21, 31 Paste for external electrodes 40, 50 External electrode component penetration part 60 Heat Treatment
Claims
1. A solid electrolyte layer; an electrode layer provided on a first surface side of the solid electrolyte layer; an external electrode provided on a first end side of the solid electrolyte layer; a buried layer provided on the first surface side of the solid electrolyte layer between the electrode layer and the external electrode; an external electrode component penetration portion that extends from the external electrode between the solid electrolyte layer and the buried layer and contains a component of the external electrode; [0023] A solid-state battery comprising:
2. 2. The solid-state battery of claim 1, wherein the external electrode component penetration portion extends between the solid electrolyte layer and the buried layer to a penetration depth of 12 μm or more from the first end.
3. the external electrode includes metal and glass; 2. The solid-state battery of claim 1, wherein the external electrode component intrusion includes components of the metal and the glass.
4. A solid electrolyte layer; an electrode layer provided on a first surface side of the solid electrolyte layer; an external electrode provided on a first end side of the solid electrolyte layer; a buried layer provided on the first surface side of the solid electrolyte layer between the electrode layer and the external electrode; A method for producing a solid-state battery comprising: forming the external electrode by performing a heat treatment on the first end side of the solid electrolyte layer having the electrode layer and the buried layer provided on the first surface side; The step of forming the external electrodes includes: A method for manufacturing a solid-state battery, comprising: forming an external electrode component insertion portion that extends from the external electrode between the solid electrolyte layer and the buried layer, the external electrode component insertion portion including a component of the external electrode.
5. The method for manufacturing a solid-state battery according to claim 4 , wherein the step of forming the external electrode component penetration portion includes a step of changing a penetration depth of the external electrode component penetration portion from the first end depending on conditions of the heat treatment.
Citation Information
Patent Citations
All-solid lithium ion secondary battery
JP2017182945A
solid-state batteries
JP2023022219A